Serverless computing in Azure with .NET : design, build, test and automate deployment, and more - Rosenbaum, Sasha (Packt Publishing, 2017)
Harness the power of the Cloud, leveraging the speed and scale of Azure Serverless computing About This Book Take advantage of the agility, scale, and cost-effectiveness of the cloud using Azure Serverless compute Build scalable, reliable, and cost-effecient applications with Serverless architecture and .NET Learn to use Azure functions to their fullest potential in .NET Who This Book Is For This book is for .NET developers who would like to learn about serverless architecture. Basic C# programming knowledge is assumed. What You Will Learn Understand the best practices of Serverless architecture Learn how how to deploy a Text Sentiment Evaluation application in an Azure Serverless environment Implement security, identity, and access control Take advantage of the speed of deployment in the cloud Configure application health monitoring, logging, and alerts Design your application to ensure cost effectiveness, high availability, and scale In Detail Serverless architecture allows you to build and run applications and services without having to manage the infrastructure. Many companies have started adopting serverless architecture for their applications to save cost and improve scalability. This book will be your companion in designing Serverless architecture for your applications using the .NET runtime, with Microsoft Azure as the cloud service provider. You will begin by understanding the concepts of Serverless architecture, its advantages and disadvantages. You will then set up the Azure environment and build a basic application using a sample text sentiment evaluation function. From here, you will be shown how to run services in a Serverless environment. We will cover the integration with other Azure and 3rd party services such as Azure Service Bus, as well as configuring dependencies on NuGet libraries, among other topics. After this, you will learn about debugging and testing your Azure functions, and then automating deployment from source control. Securing your application and monitoring its health will follow from there, and then in the final part of the book, you will learn how to Design for High Availability, Disaster Recovery and Scale, as well as how to take advantage of the cloud pay-as-you-go model to design cost-effective services. We will finish off with explaining how azure functions scale up against AWS Lambda, Azure Web Jobs, and Azure Batch compare to other types of compute-on-demand services. Whether you've been working with Az...